(untitled) - Chance, Don M. (Hoboken, N.J., 2008)
This book provides up-to-date and detailed coverage of various financial products related to derivatives and contains completely new chapters covering subjects that include why derivatives are used, forward and futures pricing, operational risk, and best practices.
Keywords: Chứng khoán phái sinh,Derivative securities,Risk management,Investments,Investments,Quản trị rủi ro,Đầu tư